The immediate results of surgical treatment of coronary heart disease complicated with left ventricular aneurysm and mitral insufficiency - V. I. Ursulenko; A. V. Kupchinsky; S. A. Rudenko; M. N. Moroz; E. V. Iuvchyk; K. V. Yashchuk (Ukrainian Journal of Cardiovascular Surgery, 2016)
Coronary heart disease is a fairly common cause of mitral regurgitation. In atherosclerosis of the coronary arteries changes of the mitral valve and mitral regurgitation of varying severity occur in 30% of patients.Subjects were 32 consistently performed at the National Institute of Cardiovascular Surgery them. Amosov NAMS of Ukraine Associated coronary bypass surgery, surgery on left ventricular aneurysm and mitral valve during the period from 1 January 2012 to 31 December 2015. It should be noted that the majority of patients (75%), the operation was performed on the heart is stopped using cardioplegia. Correction concomitant mitral insufficiency was performed using plastic techniques (with preservation of subvalvular structures) and mitral valve replacement.